Increased death and exhaustion of CD69high T cells and NK cells are associated with PD-1 antibody application in the in vitro co-culture system - Wang, Ying; Sun, Zhengyi; Du, Xue; Yu, Qiuyang; Sun, Chao; Huang, Jing; Wang, Liying (PeerJ, 2023)
Background The application of PD-1 monoclonal antibody (mAb) helps to treat non-small cell lung cancer, but acquired resistance has emerged in clinical practice. We tested the hypothesis that acquired resistance of anti-PD-1 immunotherapy is linked to death and exhaustion of activated T and NK cell. Methods The co-culture system of HCC827 cells and peripheral mononuclear cells (PBMCs) was established to evaluate the effect of PD-1 mAb on the death rate and exhaustion of T and NK cell. The predisposing role of CD69 for death and exhaustion was validated by using PHA-activated PBMCs of CD69low NSCLC patients. The 10-colour/three laser flow cytometer was used to test related markers for cell activation, death and exhaustion. Results We found that PD-1 mAb increase the death and exhaustion of T cells and NK cells in a dose-dependent way when PBMCs from NSCLC patients whose the percentages of CD69+ cells in peripheral blood T cells were greater than 5% (CD69high NSCLC patients). By analyzing PBMCs from healthy volunteers and CD69low NSCLC patients, we found that T cells and NK cells can be induced to die by PD-1 mAb after PHA activation, and had a tendency to raise the rate of cell exhaustion. Conclusions Our findings imply that increased death and exhaustion of CD69high T cells and NK cells are associated with ineffective anti-PD-1 immunotherapy in lung cancer. The CD69 expression of T cells and NK cells may be developed as a potential predictor for acquired resistance of anti-PD-1 immunotherapy. These data may provide ideas to guide individualized medication of PD-1 mAb in NSCLC patients.
Keywords: PD-1 monoclonal antibody; Acquired resistance; T cells; Natural killer cells; Tumor microenvironment